Application of dexmedetomidine for lung injury in elderly patients undergoing one-lung ventilation - Shi, Zhi-Guo; Mi, Wei-Dong (Archives of medical science, 2023)
This study aimed to evaluate the effects of dexmedetomidine (DEX) on lung injury, the oxygenation index and perioperative pulmonary complications in elderly patients who underwent thoracotomy with one-lung ventilation (OLV).IntroductionThis study aimed to evaluate the effects of dexmedetomidine (DEX) on lung injury, the oxygenation index and perioperative pulmonary complications in elderly patients who underwent thoracotomy with one-lung ventilation (OLV).A total of 120 elderly patients with lung cancer were included in the present study. According to the random number table method, these patients were randomly divided into two groups: group D and group C. Patients in group D were intravenously pumped with 0.5 μg/kg/h of DEX before anesthesia. The infusion was completed within 15 min, and anesthesia was induced by venous injection. Patients in group C were pumped with equal volumes of normal saline.Material and methodsA total of 120 elderly patients with lung cancer were included in the present study. According to the random number table method, these patients were randomly divided into two groups: group D and group C. Patients in group D were intravenously pumped with 0.5 μg/kg/h of DEX before anesthesia. The infusion was completed within 15 min, and anesthesia was induced by venous injection. Patients in group C were pumped with equal volumes of normal saline.At T2 and T3, compared with group C, group D had a significant decrease in cardiac index, mean arterial pressure and central venous pressure (p < 0.05). At T2, T3 and T4, compared with group C, group D had a significant increase in pH and PaO2 (p < 0.05). At T2, T3 and T4, compared with group C, group D had a significant decrease in Qs/Qt (p < 0.05). At T6, compared with group C, group D had a significant decrease in the supernatant of bronchoalveolar lavage fluid of tumor necrosis factor-α and interleukin 6 (p < 0.05). At T5, compared with group C, group D had a significant decrease in Visual Analogue Scale score (p < 0.05), and a significant increase in Ramsay Sedation Scale score (p < 0.05), and the number of respiratory and cardiovascular events also decreased (p < 0.05).ResultsAt T2 and T3, compared with group C, group D had a significant decrease in cardiac index, mean arterial pressure and central venous pressure (p < 0.05). At T2, T3 and T4, compared with group C, group D had a significant increase in pH and PaO2 (p < 0.05). At T2, T3 and T4, compared with group C, group D had a significant decrease in Qs/Qt (p < 0.05). At T6, compared with group C, group D had a significant decrease in the supernatant of bronchoalveolar lavage fluid of tumor necrosis factor-α and interleukin 6 (p < 0.05). At T5, compared with group C, group D had a significant decrease in Visual Analogue Scale score (p < 0.05), and a significant increase in Ramsay Sedation Scale score (p < 0.05), and the number of respiratory and cardiovascular events also decreased (p < 0.05).In elderly patients, dexmedetomidine can reduce Qs/Qt and increase PaO2 during OLV in surgery. It can reduce lung injury. Moreover, DEX reduced respiratory and cardiovascular complications in the perioperative period.ConclusionsIn elderly patients, dexmedetomidine can reduce Qs/Qt and increase PaO2 during OLV in surgery. It can reduce lung injury. Moreover, DEX reduced respiratory and cardiovascular complications in the perioperative period.